The treatment with sGC stimulator improves survival of hypertensive rats in response to volume-overload induced by aorto-caval fistula - Gawrys, Olga; Husková, Zuzana; Škaroupková, Petra; Honetschlägerová, Zuzana; Vaňourková, Zdeňka; Kikerlová, Soňa; Melenovský, Vojtěch; Bačová, Barbara Szeiffová; Sykora, Matúš; Táborský, Miloš; Červenka, Luděk (Naunyn-Schmiedeberg's archives of pharmacology, 2023)
Heart failure (HF) has been declared as global pandemic and current therapies are still ineffective, especially in patients that develop concurrent cardio-renal syndrome. Considerable attention has been focused on the nitric oxide (NO)/soluble guanylyl cyclase (sGC)/cyclic guanosine monophosphate (cGMP) pathway. In the current study, we aimed to investigate the effectiveness of sGC stimulator (BAY41-8543) with the same mode of action as vericiguat, for the treatment of heart failure (HF) with cardio-renal syndrome. As a model, we chose heterozygous Ren-2 transgenic rats (TGR), with high-output heart failure, induced by aorto-caval fistula (ACF). The rats were subjected into three experimental protocols to evaluate short-term effects of the treatment, impact on blood pressure, and finally the long-term survival lasting 210 days. As control groups, we used hypertensive sham TGR and normotensive sham HanSD rats. We have shown that the sGC stimulator effectively increased the survival of rats with HF in comparison to untreated animals. After 60 days of sGC stimulator treatment, the survival was still 50% compared to 8% in the untreated rats. One-week treatment with sGC stimulator increased the excretion of cGMP in ACF TGR (109 ± 28 nnmol/12 h), but the ACE inhibitor decreased it (-63 ± 21 nnmol/12 h). Moreover, sGC stimulator caused a decrease in SBP, but this effect was only temporary (day 0: 117 ± 3; day 2: 108 ± 1; day 14: 124 ± 2 mmHg). These results support the concept that sGC stimulators might represent a valuable class of drugs to battle heart failure especially with cardio-renal syndrome, but further studies are necessary.
Keywords: Guanylate Cyclase; lidé; Cyclic GMP; hypertenze; Heart Failure; Fistula; krysa rodu Rattus; srdeční selhání; Cardio-Renal Syndrome; guanylátcyklasa; Rats, Transgenic; Humans; guanosinmonofosfát cyklický; oxid dusnatý; Heart failure; BAY41-8543; sGC stimulator; potkani transgenní; Hypertension; zvířata; Rats; kardiorenální syndrom; píštěle; Animals; Vericiguat; cGMP; Soluble Guanylyl Cyclase; Nitric Oxide; ACF; rozpustná guanylátcyklasa